2014
DOI: 10.1002/adma.201305698
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Memory of Polymer Networks under Stress

Abstract: Generally reversible stimuli-responsive materials do not memorize the stimulus. In this study we describe an example in which stretched and constrained semi-crystalline polymer networks respond to solvent gases with stress and simultaneously memorize the concentration and the chemical nature of the solvent itself in their microstructure. This written solvent signature can even be deleted by temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Intriguingly, recent study has shown that polymer crystals formed via strain-induced crystallization can be manipulated to precisely tune the melting temperature [312][313][314]. This may open up new ways to induce 2W-SME.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent study has shown that polymer crystals formed via strain-induced crystallization can be manipulated to precisely tune the melting temperature [312][313][314]. This may open up new ways to induce 2W-SME.…”
Section: Discussionmentioning
confidence: 99%
“…One way to achieve such networks is cross‐linking of linear homo‐ or copolymers. Polyethylene (PE), natural rubber (NR), ethylene vinyl acetate (EVA), ethylene propylene diene rubber (EPDM), and many others can be cross‐linked using peroxide, siloxane, or radiation curing . Unfortunately, cross‐linking of polypropylene, a mass polymer with remarkable mechanical properties, is more complicated due to the presence of tertiary C‐atoms .…”
Section: Introductionmentioning
confidence: 99%
“…We found that constrained SMNR generates reversible mechanical stress when exposed to solvent vapor which is proportional to the solvent concentration . We could further show that constrained SMNR is capable of memorizing the chemical nature of a solvent vapor and its concentration within its microstructure measurable by irreversible stress‐answer . It is known that the microstructure particularly the polymer crystal‐size and ‐distribution is controlling the trigger‐temperature and ‐range.…”
Section: Introductionmentioning
confidence: 66%